The catch 22 of condoms in US correctional facilities - Tulsky Jacqueline P; Chang Suzanne W; Tucker Joseph D (BMC, 2007)
Abstract Background Despite the high prevalence of sexually transmitted infections (STIs) and HIV infection in US correctional settings, most jails and prisons in the United States prevent inmates from using condoms to prevent STIs/HIV. Discussion This article makes the following arguments to justify a scalable and feasible next step in the prevention of HIV/STIs among inmates: condoms are a basic and essential part of HIV/STI prevention, HIV/STI transmission occurs in the context of corrections, and several model programs show the feasibility of condom distribution in prisons. A lower end estimate for HIV incidence among incarcerated applied to 2,000,000 new inmates annually results in thousands of new HIV infections acquired each year in corrections that could be prevented with condoms in corrections facilities. Programs from parts of the United States, Canada, and much of Europe show how programs distributing condoms in correctional facilities can be safe and effective. Summary Public health and corrections officials must work together to ensure that condoms and broader sexual disease prevention programs are integrated into US jail and prison health systems.